The integration of library instruction in the middle school curriculum at the International School - Cayabyab, Maria Luz A.; Picache, Ursula G. (Quezon City : Institute of Library Science, University of the Philippines Diliman, 1976)
The study aimed to design a workable program to serve as a guide for the librarian teaching students to develop the concepts and skills necessary for the comprehension, and for the independent and effective use of the Media Center.
This proposed program is not intended as a perfect model to be initiated without deviation. This proposal is aimed towards effective learning in a specifically defined community - the Middle School at the Internation School. As shown in Chapter IV, the main part of the text, the proposed instruction starts by introducing the students to the Media Center - the nature of its collection, and the special services of its staff. The lessons are organized such that the students will develop a feeling of confidence in the use of the Media Center facilities and resources. They should know the research potential of the card catalog; have the ability to mine information from the more common indexing tools; and have the basic knowledge of the reference tools and how these resources may be used to their best advantage.
Each lesson is presented in terms of behavioral objectives to be achieved; materials and how these are to be used are presented; suggestions are offered for meeting the objectives and for evaluating the lessons. There are several optional activities. To be able to evaluate the outcome of each frame immediate feedback from the students concerning the adequacy of their performance is provided for.
Presentation has been developed to be as concrete and relevant as possible, providing opportunities for using the library skills learned inpurposeful and meaningful situations. Such is necessary to assure that mastery is obtained and library habit established.
The integration of library instruction in the curriculum can be realized with the effective collaboration of the librarian with the faculty in teaching library skills and working together in the library and in the classroom.
Mimeographed.
Vita.
Special Problem (Master of Library Science)--University of the Philippines Diliman
Keywords: Instructional materials centers; Library orientation